An Analysis Politeness Strategies in Characters Utterances in The School for Good and Evil movie - Pramadiasta, Almira; Garnida, Susie Chrismalia (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
Pragmatics is a subfield of linguistics that studies communication. Politeness is a key concept in linguistics and social interactions, referring to the strategies and behaviors people use to show respect, consideration, and deference to others. As suggested by Brown and Levinson (1987), the strategy of politeness has been observed to operate as a regressive measure towards face-threatening actions (FTA). This research aims to analyze the types of politeness strategies and find out the mostly used type of politeness strategies in The School for Good and Evil movie. This research uses a descriptive qualitative method. The researcher used Brown and Levinson (1987) theory of politeness strategies. The form of data are utterances of the characters, indicating politeness strategies. The result of this research is 79 data utterances types of politeness strategies which is divided into: bald-on record strategy (25) times, positive politeness strategy (27) times, negative politeness strategy (15) times, and off-record strategy (12) times. Politeness strategies are the mostly used in this movie is positive politeness strategies, because the speaker and the hearer have a close relationship.